1981
DOI: 10.1093/ajcn/34.8.1489
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship of thyroid hormones with vitamin A and zinc nutritional status in patients with chronic hepatic and gastrointestinal disorders

Abstract: To define the role of vitamin A, retinol binding protein, and zinc deficiency in producing the thyroid hormone abnormalities found in chronic illness, we studied 62 clinically stable patients with hepatic and gastrointestinal disorders. Serum triiodothyronine (T3) and free T3 index (FT3I) were depressed compared to controls (p less than 0.05) in the patients. Retinol binding protein and prealbumin levels correlated with both T3 and FT3I (p less than 0.01), whereas vitamin A levels did not. Vitamin A therapy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Growth retardation due to Zn deficiency in guinea-pigs as observed in the present study has also been reported in other species of animals [14], This might be due to impair ment of DNA synthesis since during Zn defi ciency the enzymes (thymidine kinase and DNA polymerase) and a hormone, somato medin C, required for DNA synthesis have been reported to be decreased [14,15], Sec ondly, hypothyroidism might have also con tributed to growth retardation [14], Lower values of serum T3 and T4 observed in ZnD guinea-pigs of the present study have also been found to be associated with Zn defi ciency in rats [2,3,5,16,17] and human beings [ 18]. Alteration in thyroid hormones as suggested by Morley et al [ 1 ] and Fujimoto et al [3] might partly be secondary to deficiency of vitamin A [19] which has been reported to be required for extrathyroidal conversion of T4 to T;, in the liver. Indeed the interaction between Se and I with respect to T4 and T3 conversion has been reported [20] but a recent study [5] on Zn and I interaction revealed that Zn deficiency did not influence thyroid hor mone metabolism in iodine-deficient rats.…”
Section: Zinc Deficiency and Thyroidsupporting
confidence: 53%
See 1 more Smart Citation
“…Growth retardation due to Zn deficiency in guinea-pigs as observed in the present study has also been reported in other species of animals [14], This might be due to impair ment of DNA synthesis since during Zn defi ciency the enzymes (thymidine kinase and DNA polymerase) and a hormone, somato medin C, required for DNA synthesis have been reported to be decreased [14,15], Sec ondly, hypothyroidism might have also con tributed to growth retardation [14], Lower values of serum T3 and T4 observed in ZnD guinea-pigs of the present study have also been found to be associated with Zn defi ciency in rats [2,3,5,16,17] and human beings [ 18]. Alteration in thyroid hormones as suggested by Morley et al [ 1 ] and Fujimoto et al [3] might partly be secondary to deficiency of vitamin A [19] which has been reported to be required for extrathyroidal conversion of T4 to T;, in the liver. Indeed the interaction between Se and I with respect to T4 and T3 conversion has been reported [20] but a recent study [5] on Zn and I interaction revealed that Zn deficiency did not influence thyroid hor mone metabolism in iodine-deficient rats.…”
Section: Zinc Deficiency and Thyroidsupporting
confidence: 53%
“…In human beings, its defi ciency in natural cases has been reported to influence thyroid status [ 1], but very little work has been done experimentally in guineapigs to prove its role in the functioning of thy roid gland. However, in rats some workers [2][3][4][5] have shown that Zn deficiency decreased serum concentrations of thyroid hormones without indicating any pathological changes in thyroid gland itself.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the level of plasma zinc has been found to be correlated with plasma T 3 and T 4 levels (Nishi et al, 1980;Aihara et al, 1984). However, Morley et al (1981) found no correlation between serum zinc and T 4 level in alcoholic cirrhotic patients. Zinc, in addition to its participation in protein synthesis, is involved in T 3 binding to its nuclear receptor (Miyamoto et al, 1991).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, naturally occurring zinc deficiency has been reported to influence thyroid status in humans (Morley et al, 1981). Considering these facts, we thought that the effect of zinc on the metabolism of the thyroid gland should be understood better in order to expand the existing knowledge concerning thyroid physiology.…”
mentioning
confidence: 99%
“…Theoretically, zinc deficiency and also reduced renal clearance of Prl [13] might both contribute to the hyperprolactinemia in renal failure. One group of zinc-deficient patients did have mod est hyperprolactinemia, although this increase may have been multifactorial [16]. Zinc deficiency has been associated with several endocrine disorders [9,15], but Prl levels have not been reported.…”
Section: Discussionmentioning
confidence: 98%